2017
DOI: 10.1016/j.archoralbio.2016.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Age-related periodontitis and alveolar bone loss in rice rats

Abstract: Objective To characterize in rice rats: (a) periodontitis (PD) progress with feeding of standard laboratory rat chow (STD) during ages 4–80 weeks; and (b) PD progress with feeding of a high sucrose-casein (H-SC) diet during young adulthood. Methods One group (N = 12) was euthanized at age 4 weeks (Baseline). Four groups (N = 8–16) consumed a STD diet from baseline and were necropsied at ages 22, 30, 52, and 80 weeks. Three groups (N= 10–16) consumed an H-SC diet from baseline. Two were necropsied at ages 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…CEJ–ABC distance is used as parameter for measurement of periodontal breakdown [18]. Furcation involvement is known to be affected by the presence of periodontal diseases: a large value indicates more extensive alveolar bone loss [19]. In this study, we confirmed that ligation surrounding the teeth causes significant gingival tissue damage and alveolar bone loss, and it increase the CEJ–ABC distance and furcation involvement.…”
Section: Discussionsupporting
confidence: 78%
“…CEJ–ABC distance is used as parameter for measurement of periodontal breakdown [18]. Furcation involvement is known to be affected by the presence of periodontal diseases: a large value indicates more extensive alveolar bone loss [19]. In this study, we confirmed that ligation surrounding the teeth causes significant gingival tissue damage and alveolar bone loss, and it increase the CEJ–ABC distance and furcation involvement.…”
Section: Discussionsupporting
confidence: 78%
“…The housing rooms were maintained at 20–26ºC with humidity of 30%–70% and a 12:12 hr light:dark cycle, or 14:10 hr cycle for breeders (Aguirre et al, ). Experimental animals ate pelleted, semi‐purified HSC diet (TestDiet 5SXA AIN‐93G w/no Complex Carbohydrates; Smelt Feed and Pet Supply, Tampa, FL, USA), which can be fed for up to 30 weeks without inducing significant metabolic abnormalities (Aguirre et al, ). This diet is based on the formula of the powdered Harvard high sucrose 700 diet and the ration 100 diet previously used to accelerate generalized PD in rice rats (Auskaps et al, ; Gotcher & Jee, ; Gupta & Shaw, ; Ryder, ).…”
Section: Methodsmentioning
confidence: 99%
“…The rat PD Score is the highest quadrant PD score for that animal. Alveolar bone height (ABH) was assessed in both maxillae and mandibles by measuring the distance between the cementoenamel junction (CEJ) and the crest of the alveolar bone, as previously described (Figure d) (Aguirre, Akhter, Kimmel, Pingel, Williams et al, ; Aguirre et al, ). Measurements were made in one section from the lingual aspect of the M1M2 interdental space.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we did not investigate non-airway epithelia, it is interesting to consider that ion transport properties of other epithelia, such as the gingival epithelia, might also be distinct and/or modified compared to other animals. If so, then perhaps those properties contribute to the well-described predilection of periodontitis in the rice rat (Aguirre et al, 2017;Gotcher and Jee, 1981a, b;Gupta and Shaw, 1956a, b).…”
Section: Discussionmentioning
confidence: 99%